A supported nano-palladium-gold catalyst and preparation method thereof

By uniformly supporting palladium and gold particles on FeOx/Al2O3 support and pretreatment of sulfides, the prepared supported nanopalladium-gold catalyst solves the problems of decreasing catalytic CO activity and poor sulfur resistance in the prior art, achieving the problem of achieving It has efficient CO catalytic oxidation and good sulfur resistance.

CN116459844BActive Publication Date: 2025-02-14RES INST OF CHEM DEFENSE PLA ACAD OF MILITARY SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310386198.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-12
Publication Date
2025-02-14
Estimated Expiration
2043-04-12

AI Technical Summary

Technical Problem

The existing supported nanogold catalysts have reduced catalytic CO activity in the presence of sulfides and have poor sulfur resistance, which limits their application in industrial flue gas treatment.

Method used

The preparation method of supported nanopalladium-gold catalyst was adopted, and the palladium and gold particles were uniformly supported on the FeOx/Al2O3 support by impregnation method and deposition precipitation method, and the sulfur resistance of the catalyst was improved by sulfide pretreatment.

Benefits of technology

The palladium and gold supported by the supported nanopalladium-gold catalyst are uniformly loaded and have high dispersion, good CO catalytic activity and stability, and can maintain efficient catalytic performance in the presence of SO2 and H2S.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116459844B_ABST
    Figure CN116459844B_ABST
Patent Text Reader

Abstract

The invention provides a supported nano palladium-gold catalyst and a preparation method thereof. The nano Au particles and nano Pd particles on the supported nano Pd-Au catalyst prepared by the invention are uniformly loaded and highly dispersed, and are easy to prepare on a large scale. The supported nano palladium-gold catalyst prepared by the invention has a good catalytic effect, can achieve full conversion of CO at -30°C, has good sulfur resistance and stability, and can still maintain a space velocity of 1346 h after SO2 treatment for 1 h and H2S treatment for 1 h. ‑1 , the CO concentration of 20000 ppm is maintained within a conversion rate drop of less than 2% in 726 minutes; the supported nano Pd-Au catalyst prepared by the present invention can be widely used in an environment where sulfides exist and can maintain long-term stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst application, and specifically relates to a supported nano palladium-gold catalyst with good sulfur resistance and CO catalytic performance and a preparation method thereof. Background Art

[0002] Incomplete combustion of fossil fuels in the chemical industry, incomplete combustion of fires and explosions, and CO in a closed environment will cause great safety hazards to people's production and life. CO poisoning is the most common poisoning in the population, and there is no effective antidote for treatment. The pathophysiology of poisoning includes a decrease in overall oxygen transfer and inhibition of mitochondrial respiration. Therefore, it is particularly important to use efficient CO catalytic oxidation materials to remove CO to ensure human health and safety.

[0003] Since nano-gold particles were found to have excellent catalytic properties, they have been widely used in catalytic oxidation reactions. The supported nano-gold catalyst has stronger performance than other catalysts in the low (normal) temperature catalytic oxidation of CO, and can achieve full conversion of low-concentration CO at room temperature. The conditions that affect the performance of supported nano-gold catalysts mainly include the particle size of nano-gold particles, the interaction between the carrier and the nano-gold particles, etc. The preparation methods of supported nano-gold catalysts mainly include impregnation method, deposition precipitation method, co-precipitation method, chemical vapor precipitation method, liquid phase reduction method, etc. Among them, the deposition precipitation method is widely used because of its simple operation and the ability to prepare catalysts with small particle size and uniform particle distribution. The oxygen vacancies on the carrier of the supported nano-gold catalyst are the activation centers of oxygen molecules. The effective selection of the carrier is conducive to obtaining a stronger supported nano-gold catalyst. α-Fe2O3 has abundant oxygen vacancies, which can provide abundant active oxygen to the nano-gold particles during the reaction, and is an excellent carrier for supported nano-gold catalysts. When urea is used as a precipitant, urea slowly releases OH- as the temperature changes, which is conducive to the formation of Au(OH)3, and studies have shown that the formation of various gold compounds during urea-assisted deposition is conducive to increasing the loading of nano-gold particles. When chloroauric acid is used as the original solution to prepare a supported nano-gold catalyst by a deposition precipitation method, Au agglomerates during the calcination process due to the presence of residual chlorine. Ammonia washing of the catalyst can effectively prevent gold sintering by removing residual chlorine. Therefore, the preparation of supported nano-gold catalysts by urea-assisted deposition precipitation method and washing with ammonia water can obtain supported nano-gold catalysts with small particle size and uniform distribution.

[0004] The presence of sulfides in the environment will affect the activity of supported nano-gold catalysts, which seriously limits the use of nano-gold catalysts in the treatment of pollutants in industrial flue gas. In an environment where SO2 exists, the activity of supported nano-gold catalysts in catalyzing CO will be severely reduced. This may be due to the increase in the adsorption strength between Au and CO after SO2 treatment. This increase inhibits the movement of CO adsorbed on Au particles to the gold-support interface to form CO2. The poor resistance of nano-gold catalysts to sulfide poisoning has always been one of the important reasons restricting the application of nano-gold catalysts. Supported nano-Pd catalysts also have strong CO catalytic oxidation performance, but have the disadvantage of low activity under low temperature conditions. Pd-Au bimetallic supported catalysts can be used efficiently in various catalytic reactions. Jin Zhang et al. simulated the effect of the addition of Au on Pd / TiO2 during CO oxidation by theoretical calculation. The results showed that the addition of Au can inhibit the poisoning of Pd / TiO2 during CO oxidation by forming a "crown jewel" Pd-Au Stucture. However, there has been no publicly reported experimental research to explore the effect of Pd-Au / FeO x / Al2O3 on the catalytic performance of CO oxidation. Wilburn et al. used DRIFTS and TPD to show that the adsorption of SO2 by Pd-Pt alloy is related to the molar ratio of Pd:Pt, and the effect of sulfide on the catalyst performance can be weakened by adjusting the ratio of bimetallic in the bimetallic catalyst. Therefore, further systematic and in-depth experimental research was conducted to explore the effect of the ratio of Pd-Au active components on the catalytic activity and stability of CO, and the effect of Pd-Au / FeO on the catalytic activity and stability of CO in the presence of sulfide. x Effect of Pd-Au / FeO / Al2O3 catalyst on CO catalytic activity and stability, and search for the best performance of CO catalytic oxidation x / Al2O3 catalyst system is a very meaningful work. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] The invention provides a supported nano palladium-gold catalyst and a preparation method thereof, so as to achieve the supported nano palladium-gold catalyst having uniform palladium and gold loading, high dispersion, good catalytic effect, good sulfur resistance, CO catalytic activity and stability.

[0007] (II) Technical solution

[0008] In order to solve the above technical problems, the present invention provides a method for preparing a supported nano-palladium-gold catalyst, which comprises the following steps:

[0009] S1. Prepare an iron salt solution with a concentration of 0.3-0.5 mol / L, wherein the iron salt solution is ferric nitrate solution, ferric sulfate solution or ferric chloride solution;

[0010] S2, activating the metal oxide, immersing it in an iron salt solution and drying it to obtain a supported nano-palladium-gold catalyst carrier; the metal oxide is aluminum oxide, zirconium oxide, magnesium oxide, magnesium hydroxide, manganese oxide, titanium oxide, copper oxide, calcium oxide, zinc oxide or cerium oxide; 1 mL of the iron salt solution contains 1.5 to 2 g of the metal oxide;

[0011] S3, after activating the supported nano-palladium-gold catalyst carrier, placing it in a container, adding a palladium salt solution and deionized water, immersing for 30 minutes, then ultrasonically assisted immersion for 30 minutes, and shaking on a constant temperature water bath shaker at room temperature for 24 hours to obtain a supported nano-palladium catalyst precursor; the palladium salt solution is a palladium nitrate solution, a palladium chloride solution or a palladium acetate solution; the mass ratio of the nano-palladium-gold catalyst carrier to the palladium salt solution is 1: (0.01-0.03), and the volume of deionized water is 50-150 mL;

[0012] S4, taking out the supported nano-palladium catalyst precursor, and then drying, calcining in an oxygen atmosphere, and calcining in a hydrogen atmosphere in sequence to obtain a supported nano-palladium catalyst;

[0013] S5, placing a supported nano-palladium catalyst in a container, adding a precipitant, chloroauric acid, and deionized water to the container in sequence, shaking the container in a constant temperature water bath at a temperature of 75-85°C until the pH value of the solution is 8-8.5, and standing for 4-6 hours to obtain a supported nano-gold catalyst precursor; the mass ratio of the supported nano-palladium catalyst, the precipitant, chloroauric acid, and deionized water is 1:(0.9-1.0):(0.02-0.065):(8.5-12); the precipitant is urea, sodium carbonate, or sodium bicarbonate;

[0014] S6. After taking out the supported nano-gold catalyst precursor, washing, drying, calcining in an oxygen atmosphere, and calcining in a hydrogen atmosphere are performed in sequence to obtain a supported nano-palladium-gold catalyst.

[0015] Furthermore, in step S2, the specific steps of activation are: heating the metal oxide to 550-650°C at 5-15°C / min, keeping it warm for 1.5-2.5 hours and then lowering it to room temperature; the drying temperature is 120-140°C and the drying time is 10-14 hours.

[0016] Furthermore, in step S2, the shape of the metal oxide is spherical, cubic, honeycomb, rod-shaped or flake-shaped.

[0017] Furthermore, in step S3, the specific steps of activation are: heating the supported nano-palladium-gold catalyst carrier to 450-550°C at 5-15°C / min, keeping it warm for 1.5-2.5h and then lowering it to room temperature; the oscillation speed of the constant temperature water bath shaker is 80-150rpm.

[0018] Furthermore, in step S4, the drying temperature is 120-140°C, and the drying time is 10-14h; the calcination temperature in oxygen atmosphere is 280-320°C, and the time is 1.5-2.5h; the calcination temperature in hydrogen atmosphere is 280-320°C, and the time is 30-60min.

[0019] Furthermore, in step S5, the mass percentage of gold in chloroauric acid is 48-50%; and the rotation speed of the constant temperature water bath shaker is 80-150 rpm.

[0020] Further, in step S6, after taking out the supported nano-gold catalyst precursor, it is washed with 100-150 mL / time deionized water for 3-5 times and 50-80 mL / time ammonia water for 1-2 times in sequence; the drying temperature is 120-140°C, and the drying time is 10-14h; the temperature of calcination in oxygen atmosphere is 280-320°C, and the time is 1.5-2.5h; the temperature of calcination in hydrogen atmosphere is 280-320°C, and the time is 30-60min.

[0021] Furthermore, step S2 and step S3 are repeated multiple times to obtain a supported nano-gold catalyst carrier that meets the thickness requirement.

[0022] In addition, the present invention also provides a supported nano-palladium-gold catalyst, which is prepared by the above method.

[0023] In addition, the present invention also proposes an application of the above-mentioned supported nano-palladium-gold catalyst, wherein the supported nano-palladium-gold catalyst is subjected to sulfide pretreatment and then subjected to CO catalytic oxidation reaction and gas chromatography detection; wherein the sulfide pretreatment is before the catalyst catalytically oxidizes CO, after being purged with SO2 at a concentration of 2 ppm and a flow rate of 100 mL / min for 1 hour, it is then purged with H2S at a concentration of 2 ppm and a flow rate of 100 mL / min for 1 hour; when the CO conversion rate is detected as a function of temperature, the CO concentration is 2500 ppm and the flow rate is 50 mL / min; when the CO stability at room temperature is detected, the CO concentration is 20000 ppm and the volume space velocity is 1346 h / min. -1 .

[0024] (III) Beneficial effects

[0025] The invention provides a supported nano palladium-gold catalyst and a preparation method thereof. The nano Au particles and nano Pd particles on the supported nano Pd-Au catalyst prepared by the invention are uniformly loaded and highly dispersed, and are easy to prepare on a large scale. The supported nano palladium-gold catalyst prepared by the invention has a good catalytic effect, can achieve full conversion of CO at -30°C, has good sulfur resistance and stability, and can still maintain a space velocity of 1346 h after SO2 treatment for 1 hour and H2S treatment for 1 hour. -1 , the CO concentration of 20000 ppm is maintained within a conversion rate drop of 2% in 726 minutes; the supported nano Pd-Au catalyst prepared by the present invention can be widely used in an environment where sulfides exist, and can maintain long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The supported nano-palladium-gold catalyst Pd-Au / FeO prepared in Example 1 x / Al2O3 XRD test results schematic diagram; in the figure, ▼ is the peak of α-Fe2O3, is the peak of nano-Au, ◆ is the peak of γ-Al2O3; the abscissa is 2θ, unit degree;

[0027] Figure 2 a is Au / FeO with a scale of 50 nm x TEM characterization of / Al2O3 catalyst; Figure 2 b. Figure 2 c are Au / FeO x / Mapping characterization diagram of Au and Fe elements on Al2O3 catalyst; Figure 2 d is Au / FeO x / Particle size distribution of Al2O3 catalyst; Figure 2 e is Pd-Au / FeO with a scale of 50 nm x TEM characterization of / Al2O3 catalyst; Figure 2 f, 2g, 2h are Pd-Au / FeO x Characterization diagram of Au, Pd and Fe elements on / Al2O3 catalyst;

[0028] Figure 3 a is the supported nanocatalyst Pd-Au / FeO x / XEDS characterization of Al2O3 adsorption of sulfide, Figure 3 b is Au / FeO x / XEDS characterization of sulfide adsorption by Al2O3;

[0029] Figure 4 Supported nanocatalyst Pd-Au / FeO x / Al2O3 and Au / FeO x / CO-TPR characterization diagram of Al2O3;

[0030] Figure 5 Supported nanocatalyst Pd-Au / FeO x / Al2O3 and Au / FeO x Schematic diagram of the change of CO conversion rate with temperature before and after Al2O3 sulfidation;

[0031] Figure 6 Supported nanocatalyst Pd-Au / FeO x / Al2O3 and Au / FeO x Schematic diagram of the change of CO conversion rate over time before and after Al2O3 sulfidation;

[0032] Figure 7 Pd-Au / FeO with different Au and Pd mass ratios x / Al2O3 catalyst and Au / FeO x Schematic diagram of the conversion rate of CO on / Al2O3 catalyst as the temperature changes;

[0033] Figure 8 Pd-Au / FeO with different Au and Pd mass ratios x / Al2O3 catalyst and Au / FeO x Schematic diagram of the CO conversion rate of / Al2O3 catalyst after sulfidation as the temperature changes. DETAILED DESCRIPTION

[0034] In order to make the purpose, content and advantages of the present invention more clear, the specific implementation methods of the present invention are further described in detail below in conjunction with the drawings and examples.

[0035] Example 1

[0036] Supported Nano-palladium-gold Catalyst Pd-Au / FeO x / Preparation method of Al2O3

[0037] S1. Prepare a 0.4 mol / L ferric nitrate (FeN3O9·9H2O) solution;

[0038] S2. Take spherical aluminum oxide with a diameter of 2 mm and put it in a crucible and put it in a muffle furnace. Heat it to 600°C at a rate of 10°C / min, keep it warm for 2 hours and then lower it to room temperature to obtain activated aluminum oxide. According to a volume ratio of 1:1, immerse the activated aluminum oxide in ferric nitrate solution, put it in an oven at 120°C and dry it for 12 hours. After taking it out, put it in a muffle furnace and heat it to 500°C at a rate of 10°C / min. Keep it warm for 2 hours and then lower it to room temperature to obtain once-impregnated FeOx / Al2O3 carrier;

[0039] S3, repeat step 2 twice to obtain three-impregnation FeO x / Al2O3 carrier;

[0040] S4, take FeO x / Al2O3 carrier 10g was placed in a conical flask, palladium nitrate containing 0.1g of palladium was added, and the volume was adjusted to 50mL. After standing for 30min, ultrasonic-assisted impregnation was performed for 30min. The conical flask was then placed in a constant temperature water bath shaker and oscillated at 135rpm for 24h to obtain a supported nano-palladium catalyst precursor.

[0041] S5. After the reaction is completed, the sample is taken out and dried for 12 hours; the dried sample is placed in a tube furnace and calcined at 300°C for 2 hours in an oxygen atmosphere and then calcined at 300°C for 30 minutes in a hydrogen atmosphere to obtain Pd / FeO x / Al2O3 catalyst;

[0042] S6, according to the mass ratio of 1:1:0.042:10, Pd / FeO x / Al2O3 catalyst, urea, chloroauric acid with a gold content of 48% and deionized water are added to a conical flask in sequence, and the conical flask is placed in a constant temperature water bath shaker, shaken at a speed of 130 rpm and heated to 80°C. When the pH value of the solution is 8, the shaking and heating are stopped and the solution is allowed to stand for 4 hours to obtain a supported nano-palladium-gold catalyst precursor;

[0043] S7, take out and wash the supported nano palladium-gold catalyst precursor, first wash it with 120mL / time deionized water for 4 times, then wash it with 60mL / time ammonia water for 2 times, until no precipitation is produced when tested with 0.5mol / L silver nitrate solution; put the washed catalyst into an oven and dry it at a temperature of 120°C for 12h; put the sample obtained after drying into a tubular furnace and calcine it at 300°C in an oxygen atmosphere for 2h, and then calcine it at 300°C in a hydrogen atmosphere for 30min, to obtain a supported nano palladium-gold catalyst Pd-Au / FeO x / Al2O3, where the mass ratio of Au:Pd is 2:1.

[0044] The supported nano-palladium-gold catalyst Pd-Au / FeO prepared in this example x The test results of the loading capacity of the active components palladium and gold of / Al2O3 (ICP-OES) showed that the theoretical loading capacity of Pd and Au was 1% and 2%, and the actual loading capacity was 0.7% and 1.7%. The theoretical loading capacity was close to the actual loading capacity, indicating that the catalyst prepared in this embodiment has a good loading effect and a high raw material utilization rate.

[0045] The supported nano-palladium-gold catalyst Pd-Au / FeO prepared in this example x / Al2O3 crystal structure test results reference Figure 1 Sharp peaks of aluminum oxide and iron oxide, as well as peaks of gold nanoparticles, appeared, indicating that the nanoparticles were successfully loaded on FeO x / Al2O3 support, but did not show the characteristic peak of Pd, because Pd was highly dispersed on the catalyst support.

[0046] The supported nanocatalyst Pd-Au / FeO prepared in this example x / Al2O3 and Au / FeO x / Al2O3 morphology, element distribution and particle size, such as Figure 2 As shown. Among them, Au is evenly dispersed in FeO x / Al2O3 support ( Figure 2 a and 2b). The distribution of nano-Au particles was statistically analyzed by Nano Measurer particle size distribution software, and the average particle size was calculated to be 3.5 nm ( Figure 2 d). Pd-Au / FeO x The nano-Pd particles in the / Al2O3 catalyst are relatively large and evenly dispersed, and the nano-Au particles with smaller particle sizes grow on the Pd particles ( Figure 2 e, 2f, 2g), Figure 2 c and Figure 2 h is Au / FeO x / Al2O3 catalyst and Pd-Au / FeO x / Fe element mapping characterization diagram on Al2O3 catalyst.

[0047] The supported nanocatalyst Pd-Au / FeO prepared in this example x / Al2O3 and Au / FeO x The element distribution after sulfidation of / Al2O3 is as follows Figure 3 a and 3b. By calculation, it is found that Pd-Au / FeO x / Al2O3 catalyst adsorbed 7.8wt% S, while Au / FeO x / Al2O3 catalyst adsorbs 33.66wt% S, which is Pd-Au / FeO x / Al2O3 catalyst, which is 4.3 times that of the catalyst, indicating that sulfide is not easy to form on the Pd-Au / FeO x / Al2O3 catalyst adsorption.

[0048] The supported nanocatalyst Pd-Au / FeO prepared in this example x / Al2O3 and Au / FeO x / Al2O3's oxidation capacity for CO, such as Figure 4 Pd-Au / FeO x The peaks of CO reduction and CO2 increase appeared at 243.4℃ for Au / FeO / Al2O3 catalyst, which were attributed to the oxidation of CO by the supported nano-Pd catalyst. x The peaks of CO reduction and CO2 increase appeared at 517℃ for the Pd-Au / FeO / Al2O3 catalyst, which were attributed to the oxidation of CO by the supported nano-Au catalyst. x The peak of CO catalysis by Au / FeO x / Al2O3 catalyst catalyzed CO peak shifted to lower temperature, which also indicates that Pd-Au / FeO x / Al2O3 catalyst has higher low-temperature catalytic CO activity.

[0049] The supported nanocatalyst Pd-Au / FeO prepared in this example x / Al2O3 and Au / FeO x / Al2O3, without sulfide pretreatment, can achieve full conversion of 2500ppm CO at -30℃, such as Figure 5 After sulfide pretreatment, Pd-Au / FeO x The conversion rate of Au / FeO / Al2O3 catalyst to 2500ppm CO at -30℃ was 87.2%. The conversion rate reached 100% at 25℃ and remained at 100% as the temperature increased. x / Al2O3 catalyst maintained a conversion rate of 23% to 26% with temperature change, and its conversion rate was significantly lower than that before sulfidation, which indicates that Pd-Au / FeO x / Al2O3 catalyst is less affected by sulfides.

[0050] The supported nanocatalyst Pd-Au / FeO prepared in this example x / Al2O3 and Au / FeO x / Al2O3, the test results of CO catalytic oxidation stability at 25℃ before and after sulfide treatment, such as Figure 6 As shown. Without sulfide pretreatment, Au / FeO x The conversion rate of Pd-Au / FeO / Al2O3 catalyst decreased from 97.9% to 52.4% within 726 min. x The conversion rate of Au / FeO / Al2O3 catalyst decreased from 100% to 97.9% within 748 min. xThe conversion rate of Pd-Au / FeO / Al2O3 catalyst decreased from 91.9% to 37% within 550 min. x The conversion rate of the Pd-Au / FeO / Al2O3 catalyst decreased from 98.1% to 96.5% within 726 min. x / Al2O3 catalyst has very strong stability before and after sulfide treatment.

[0051] Example 2

[0052] This embodiment is basically the same as embodiment 1, except that Pd / FeO x The mass ratio of Au:Pd mass ratio of 1:1 was 1:1. x / Al2O3 catalyst.

[0053] Example 3

[0054] This embodiment is basically the same as embodiment 1, except that Pd / FeO x The mass ratio of Au:Pd / FeO / Al2O3 catalyst, urea, chloroauric acid with 48% gold content and deionized water was 1:1:0.063:10, and Pd-Au / FeO with a mass ratio of Au:Pd of 3:1 was prepared. x / Al2O3 catalyst.

[0055] Example 4

[0056] This embodiment is basically the same as embodiment 1, except that Pd / FeO x The mass ratio of Au:Pd / FeOx / Al2O3 catalyst, urea, chloroauric acid with a gold content of 48% and deionized water is 1:1:0.105:10, and a Pd-Au / FeOx / Al2O3 catalyst with a Au:Pd mass ratio of 5:1 is prepared.

[0057] Example 5

[0058] This embodiment is basically the same as embodiment 1, except that Pd / FeO x The mass ratio of Au:Pd mass ratio of 10:1 was 1:1 / Al2O3 catalyst, urea, chloroauric acid with 48% gold content and deionized water, and Pd-Au / FeO was prepared. x / Al2O3 catalyst.

[0059] The Pd-Au / FeO prepared in Examples 2 to 5 have Au:Pd mass ratios of 1:1, 3:1, 5:1, and 10:1, respectively. x / Al2O3 catalyst and Au / FeOx / Al2O3 catalyst, catalytic activity results for CO, such as Figure 7 Among them, at -30℃, except for Pd-Au / FeO with a mass ratio of Au:Pd of 10:1 x / Al2O3 catalyst, the catalytic conversion rate of CO for other catalysts reached 100%. Pd-Au / FeO with a mass ratio of Au:Pd of 10:1 x / Al2O3 catalyst also achieves complete catalytic conversion of CO at about -25°C. x / Al2O3 catalyst and Au / FeO x / Al2O3 catalysts have very good low-temperature catalytic oxidation of CO activity.

[0060] The Pd-Au / FeO prepared in Examples 2 to 5 have Au:Pd mass ratios of 1:1, 3:1, 5:1, and 10:1, respectively. x / Al2O3 catalyst and Au / FeO x / Al2O3 catalyst, catalytic activity results for 2500ppm CO after sulfidation pretreatment, such as Figure 8 When the above catalysts were pretreated with 2ppm SO2 and 2ppm H2S for 1h, the Pd-Au / FeO x / Al2O3 catalyst still achieved 100% catalytic conversion of 2500ppm CO at 20℃, while Au / FeO x The catalytic conversion rate of Pd-Au / FeO / Al2O3 catalyst to 2500ppm CO is only 25%, indicating that x / Al2O3 catalyst pair has very good stability against sulfides.

[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a supported nano-palladium-gold catalyst, characterized in that: The preparation method comprises the following steps: S1. Prepare an iron salt solution with a concentration of 0.3-0.5 mol / L, wherein the iron salt solution is ferric nitrate solution, ferric sulfate solution or ferric chloride solution; S2, after activating the metal oxide, immersing it in an iron salt solution and drying it to obtain a supported nano-palladium-gold catalyst carrier; the metal oxide is aluminum oxide, zirconium oxide, magnesium oxide, magnesium hydroxide, manganese oxide, titanium oxide, copper oxide, calcium oxide, zinc oxide or cerium oxide; 1 mL of the iron salt solution contains 1.5-2 g of the metal oxide; the specific steps of activation are: heating the metal oxide to 550-650° C. at 5-15° C. / min, keeping it warm for 1.5-2.5 hours, and then lowering it to room temperature; the drying temperature is 120-140° C., and the drying time is 10-14 hours; S3, after activating the supported nano-palladium-gold catalyst carrier, place it in a container, add palladium salt solution and deionized water, immerse for 30 minutes, then ultrasonically assisted immersion for 30 minutes, and oscillate on a constant temperature water bath shaker for 24 hours at room temperature to obtain a supported nano-palladium catalyst precursor; the palladium salt solution is a palladium nitrate solution, a palladium chloride solution or a palladium acetate solution; the mass ratio of the nano-palladium-gold catalyst carrier to the palladium salt solution is 1: (0.01-0.03), and the volume of deionized water is 50-150 mL; the specific steps of activation are: heating the supported nano-palladium-gold catalyst carrier to 450-550°C at 5-15°C / min, keeping the temperature for 1.5-2.5 hours, and then lowering to room temperature; the oscillation speed of the constant temperature water bath shaker is 80-150rpm; S4, taking out the supported nano-palladium catalyst precursor, and then drying, calcining in an oxygen atmosphere, and calcining in a hydrogen atmosphere in sequence to obtain a supported nano-palladium catalyst; S5, placing a supported nano-palladium catalyst in a container, adding a precipitant, chloroauric acid, and deionized water to the container in sequence, shaking the container in a constant temperature water bath at a temperature of 75-85° C. until the pH value of the solution is 8-8.5, and standing for 4-6 hours to obtain a supported nano-gold catalyst precursor; the mass ratio of the supported nano-palladium catalyst, the precipitant, chloroauric acid, and deionized water is 1:(0.9-1.0):(0.02-0.065):(8.5-12); the precipitant is urea, sodium carbonate, or sodium bicarbonate; S6. After taking out the supported nano-gold catalyst precursor, washing, drying, calcining in an oxygen atmosphere, and calcining in a hydrogen atmosphere are performed in sequence to obtain a supported nano-palladium-gold catalyst.

2. The preparation method according to claim 1, characterized in that In step S2, the shape of the metal oxide is spherical, cubic, honeycomb, rod-shaped or sheet-shaped.

3. The preparation method according to claim 1, characterized in that: In step S4, the drying temperature is 120-140°C and the drying time is 10-14h; the calcination temperature in oxygen atmosphere is 280-320°C and the time is 1.5-2.5h; the calcination temperature in hydrogen atmosphere is 280-320°C and the time is 30-60min.

4. The preparation method according to claim 1, characterized in that: In step S5, the mass percentage of gold in chloroauric acid is 48-50%; and the rotation speed of the constant temperature water bath shaker is 80-150 rpm.

5. The preparation method according to claim 1, characterized in that: In step S6, after taking out the supported nano-gold catalyst precursor, it is washed with 100-150 mL / time deionized water for 3-5 times and 50-80 mL / time ammonia water for 1-2 times in sequence; the drying temperature is 120-140° C. and the drying time is 10-14 h; the temperature of calcination in oxygen atmosphere is 280-320° C. and the time is 1.5-2.5 h; the temperature of calcination in hydrogen atmosphere is 280-320° C. and the time is 30-60 min.

6. The preparation method according to claim 1, characterized in that: Step S2 and step S3 are repeated multiple times to obtain a supported nano-gold catalyst carrier that meets the thickness requirement.

7. A supported nano-palladium-gold catalyst, characterized in that: The supported nano-palladium-gold catalyst is prepared by the method according to any one of claims 1 to 6.

8. An application of the supported nano-palladium-gold catalyst as claimed in claim 7, characterized in that: The supported nano-palladium-gold catalyst was subjected to sulfide pretreatment and then subjected to CO catalytic oxidation reaction and gas chromatography detection; wherein, the sulfide pretreatment was to purge SO2 with a concentration of 2 ppm and a flow rate of 100 mL / min for 1 hour before the catalyst catalytically oxidized CO, and then purge H2S with a concentration of 2 ppm and a flow rate of 100 mL / min for 1 hour; when the CO conversion rate was detected with temperature, the CO concentration was 2500 ppm and the flow rate was 50 mL / min; when the CO stability was detected at room temperature, the CO concentration was 20000 ppm and the volume space velocity was 1346 h -1 .

Citation Information

Patent Citations

  • Preparation method of CO room temperature catalyst with ultrahigh activity and moisture resistance

    CN113426459A

  • Preparation method of supported nanogold catalyst

    CN115722231A

  • One-step method for preparing compound oxide supported nano noble metal catalyst

    CN1736608A